A importância da inclusão da cultura afro-brasileira nos currículos de educação física escolar a partir do conteúdo capoeira - Silveira, Marta Iris Camargo Messias da (2004)
The objective of this work is to analyse, in a pedagogic form, the "capoeira" in order to classify it as a school content in the Physical Education discipline, creating a possibility to include the afro culture in schools. It is proposed a historical - cultural redeem because "capoeira" is one of the demonstrations that have in its origin several bases of African matrixes. This content, in the schools, would allow reflexion and debate about racial discrimination, social exclusion, public policies, affirmative actions. In the beginning of this study, it was done a matrix established in the historical and dialectical materialism view where some themes such as multiculturalism, affirmative action policies, Afro Brazilian identity, Racial Discrimination and the "Capoeira" in the educational context, were investigated. The work was built through a bibliografical and propositional approach. It is intended to redeem the black people historical contribution in the Brazilian culture development; to discuss the struggle of the Black Movement, considering its advances and retrogressions; to consider the "capoeira" as a resistent movement and to sensible the school community about the ethnic and cultural diversity in our country. It was not intended merely implant capoeira in the school and say that the culture and the true history of the black people will be respected, but codify the capoeira as a Physical Education content and extract the principal knowledge to develop critical and independent citizens, enable them to reflect and understand in which project they are, the values that guide our society and that they feel themselves historical citizens in the process of social change.